IMPACT OF MOVING THE NEW CAPITAL TO KALIMANTAN (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
Jakarta has been the capital of the country (IKN) since the days before Indonesia's independence. The enactment of Law Number 29 of 2007 concerning the Provincial Government of the Special Capital Region of Jakarta confirmed Jakarta to become the Capital city of Indonesia. The many dynamics over the years such as the issue of the capital will sink cause Jakarta to be considered no longer qualified to be a canyon capital. The emergence of the discourse on the transfer of the capital since the era of President Soekarno's administration until it was reaffirmed by the president Jokowi administration on August 26, 2019 that the Government said that it would move The State Capital from DKI Jakarta province to East Kalimantan Province. Evidenced by the issuance of Law Number 3 of 2022 concerning the National Capital which was passed by the House of Representatives (DPR) on January 18, 2022 and signed by President Joko Widodo on February 15, 2022. The policy to move IKN is motivated by the need for the development of new economic areas, reducing inequality between regions, and improving the welfare of the people. The author finds that the transfer of IKN has stronger strengths and opportunities than the weakness and threat side so that the transfer of IKN is expected to have an impact positive for the Indonesian economy.